2020
DOI: 10.20945/2359-3997000000298
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid as a predictor of endothelial dysfunction in patients with metabolic syndrome

Abstract: Objective: We conducted a study to examine the association of endothelial dysfunction and oxidative stress with uric acid levels in patients of metabolic syndrome. Subjects and methods: One hundred and two patients of Metabolic Syndrome (International Diabetes Federation definition) were included in the study. Anthropometric measurements, serum uric acid levels, fasting blood sugar levels and lipid levels, as well as malondialdehyde and reactive nitrogen intermediates were measured after an 8-hour fasting peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…As endothelial dysfunction is also a primary pathogenic mechanism of ED, hyperuricaemia‐induced endothelial impairments might play a crucial role in ED seen in hyperuricaemia patients. Previous clinical studies have indeed demonstrated that uric acid was significantly associated with endothelial dysfunction in patients with metabolic syndrome (Singh et al, 2021), and that ED was an early manifestation of systemic vascular endothelial injury (Salem et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…As endothelial dysfunction is also a primary pathogenic mechanism of ED, hyperuricaemia‐induced endothelial impairments might play a crucial role in ED seen in hyperuricaemia patients. Previous clinical studies have indeed demonstrated that uric acid was significantly associated with endothelial dysfunction in patients with metabolic syndrome (Singh et al, 2021), and that ED was an early manifestation of systemic vascular endothelial injury (Salem et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…As endothelial dysfunction is also a primary pathogenic mechanism of ED, hyperuricemia-induce endothelial impairments might play a crucial role in ED seen in hyperuricemia patients. Previous clinical studies have indeed demonstrated that uric acid was signi cantly associated with endothelial dysfunction in patients with metabolic syndrome [42], and that ED was an early manifestation of systemic vascular endothelial injury [43].…”
Section: Discussionmentioning
confidence: 95%
“…A cross-sectional study in patients with unilateral small kidney or renal agenesis conducted by Yazici et al demonstrated that the SUA level was positively correlated with arterial stiffness ( Yazici et al, 19932017 ). Mechanistic studies have shown that uric acid causes endothelial dysfunction, resulting in cardiovascular events ( Khosla et al, 2005 ; Liang et al, 2015 ; Lee et al, 2021 ; Singh et al, 2021 ). In our meta-analysis, we found that allopurinol might slightly reduce the risk of cardiovascular complications in only three RCTs.…”
Section: Discussionmentioning
confidence: 99%